(untitled) (Research Nepal Journal of Development Studies, 2019)
At this time, entire countries around the globe-regardless of size, location, political variation and differences of the past legacies- are actively engaged and have incessantly exhibited a deep penchant into discourse of development. This article tries to path find the most acceptable notion of development along with demarcation of Himalayan region. Furtherance, this writing explores way-out for the very region’s development by evidently detaining and vanquishing the existing hindrances and noticeable hurdles, which have often led the prospects of organic developmental gain regularly towards a dauntingly downward trajectory since long.